Trastuzumab-functionalized SK-BR-3 cell membrane-wrapped mesoporous silica nanoparticles loaded with pyrotinib for the targeted therapy of HER-2-positive breast cancer - Xing Liu; Wenwen Shen (International Journal of Pharmaceutics: X)
In this study, the trastuzumab-functionalized SK-BR-3 cell membrane-wrapped mesoporous silica nanoparticles loaded with pyrotinib (Tra-CM-MSN-PYR) were prepared for targeted therapy of HER2-positive breast cancer. Transmission electron microscopy (TEM) characterization showed that MSN had a spherical morphology with mesoporous channels and that the structure of Tra-CM-MSN was a cell membrane (CM) layer successfully coated on the surface of MSN. A cellular uptake assay demonstrated that FITC-labeled Tra-CM-MSN were taken up by SK-BR-3 breast cancer cells, which illustrated that Tra-CM-MSN had good targeting ability compared with CM-MSN and MSN. In vivo imaging experiments demonstrated significant accumulation of FITC-labeled Tra-CM-MSN in tumor tissues, further proving that Tra-CM-MSN have superior targeting properties. Cell apoptosis experiments suggested that Tra-CM-MSN-PYR significantly inhibited the proliferation of SK-BR-3 breast cancer cells. The results of in vivo animal experiments also showed that Tra-CM-MSN-PYR significantly inhibited tumor growth. These results indicate that Tra-CM-MSN-PYR has potential application as a targeted therapy for HER2-positive breast cancer in the future.